Pengaruh Kebijakan Dividen, Likuiditas dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Farmasi dan Riset Kesehatan Terdaftar di BEI Periode 2018-2024 (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
This study aims to analyze the effects of dividend policy, liquidity, and profitability on firm value in pharmaceutical and health research companies listed on the Indonesia Stock Exchange. Firm value is proxied using Price to Book Value (PBV), while the independent variables include Dividend Payout Ratio (DPR), Current Ratio (CR), and Return on Assets (ROA). The study population comprises all companies in the sector, with a sample size of 56 observations selected using purposive sampling. The analysis method used was multiple linear regression with the aid of SPSS software. The results indicate that, individually, DPR and CR do not have a significant effect on PBV. Conversely, ROA has a positive and statistically significant effect on firm value, suggesting that profitability is a primary consideration for investors in assessing firm value. Furthermore, the results of the simultaneous test (F-test) indicate that DPR, CR, and ROA collectively have a significant effect on PBV, with a coefficient of determination (R²) of 35.4%. These findings support signaling theory, which asserts that strong profitability performance can send positive signals to the market in determining firm value. The results of this study imply that company management should prioritize improving profitability performance as a key strategy for enhancing firm value, for example through operational efficiency, asset optimization, and product innovation. Dividend policies and liquidity management should still be maintained at optimal levels. For investors, these findings provide a basis for investment decision-making by placing greater emphasis on profitability indicators, particularly ROA, as the primary signal in assessing corporate value